An investigation into the frequency and risk factors of low back pain following surgical treatment of isolated calcaneal fractures - Dilek Bayraktar; Cengizhan Özgürbüz; Anıl Murat Öztürk; Salih Kemal Aktuğlu; Nadir Özkayın (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to determine the frequency of low back pain after calcaneal fractures treated with open reduction internal fixation (ORIF) and the risk factors that cause this condition.